Morphological and molecular characterisation of monogeneans / Tan Wooi Boon - Tan, Wooi Boon (2013)
Morphologies and morphometries as diagnostic characters are shown statistically to be able to differentiate between species and intraspecific variants. Intraspecific variants or morphovariants exist in nature but the variations they possessed are not enough to consider them as species (differentiation index values for morphovariants is 50% less than the values for species). These variations are due to genetic difference resulting from cross-fertilisations between different individuals of the same species. Such variations are necessary tools for future species diversification. The 28S rDNA are able to group members of the major dactylogyridean families together showing the monophyly of these families within the Dactylogyridea. The phylogenetic trees also indicate the heterogeneity of the monogeneans currently placed under the Ancyrocephalidae, dividing them into two groups according to their macroenvironment, freshwater and marine ecosystems with the exception of Cichlidogyrus and Scutogyrus spp. It is proposed that the two groups are separated with the freshwater members (Ancyrocephalus, Actinocleidus, Cleidodiscus, Urocleidus and Onchocleidus) remaining in Ancyrocephalidae and a new family be created to accommodate the marine members, i.e. Haliotrema, Bravohollisia, Caballeria, Pseudohaliotrema, Metahaliotrema, Euryhaliotrema, Euryhaliotrematoides, Tetrancistrum, Haliotrematoides, Ligophorus and Aliatrema as well as freshwater members from the cichlids, i.e. Cichlidogyrus, Scutogyrus and Onchobdella. The cichlid hosts have been postulated to have a marine origin. This analysis seems to confirm the familial status of Heteronchocleididae, Ancylodiscoididae, Neocalceostomatidae and Pseudodactylogyridae. However the positions of the different monogeneans in phylogenetic trees do not correspond with the hypothesized evolutionary history of the morphological characteristics of the different dactylogyridean groups in particular the 2- and 4-anchor monogeneans. The host relationships based on Cytochrome b and monogenean relationships based on 28S rDNA support the well established parasitophyletic rule that related host species harbours related monogenean parasites. The specificity of some monogenean species suggests they have co-evolved and co-speciated within their host groups. However there are cases of monogenean being acquired via host transfer: for example Dactylogyrus spp. from a cyprinid host are probably acquired by an anadromous marine fish and the subsequent speciation of the Dactylgoyrus spp. on the marine fish Lateolabrax sp. give rise to the present distribution patterns of Dactylogyrus. Besides host transfer, some monogeneans species might have failed to speciate and this is probably what happened in the case of some species of heteronchocleidids on the anabantoid-channid fish group. This study shows that for a good statistical differentiation of the species and morphovariants, large morphometric data sets are necessary. The same is true when molecular data is used, one of the limitation in this thesis is the absence of some genera (Dogielus and Thaparogyrus are not represented in the Dactylgoyridae) and the lack of species representation in some (Pseudomurraytrematidae is represented by one species.). This study also notes the limitation of depending solely on 28S rDNA for reconstructing phylogenetic relationships.